(untitled) (Revista Electrónica REDINE, 2026)
The purpose of this article is to understand how students in the Human Development Program at the Universidad Centroccidental Lisandro Alvarado perceive the teaching-learning process in the course on Biosociantropology. The methodology employed was based on a qualitative approach, the principles of the interpretive paradigm, and the application of the hermeneutic method, combined with the processing and systematization of the collected information. At the conclusion of the study, it is recommended that the teaching-learning process for dense and abstract courses such as Biosociantropology requires comprehensive reading and writing activities in the classroom, lectures, and teamwork with other concrete courses.